1998
DOI: 10.1017/s1138741600005357
|View full text |Cite
|
Sign up to set email alerts
|

Selective Processing of Food– and Body–Related Information and Autonomic Arousal in Patients with Eating Disorders

Abstract: Both atteníional bias (using the tuodified Stroop Task) ami autonomic reactivity (skin conductance level) to food-aud body-related information v.'ere assessed in 25 patients with eating disorders (15 patients with anorexia, 10 patients with bulimia) amI 18 women controis. Patients with anorexia showed Ihe greatest inrerference in color-naming foodrelated words. However, on Ihis occasion there were no difierences in body condition, probably because of heterogeneity of clinical samples and because the control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Among studies using the Stroop task with food-related cues, the majority of studies found no significant differences in AB between women with BN and healthy controls (Black, Wilson, Labouvie, & Heffernan, 1997; Davidson & Wright, 2002; Flynn & McNally, 1999; Johansson, Carlbring, Ghaderi, & Andersson, 2008; Lee, Namkoong, & Jung, 2017; Lovell, Williams, & Hill, 1997; Perpiñá, Hemsley, Treasure, & de Silva, 1993; Perpiña, Leonard, Treasure, Bond, & Banos, 1998; Ruiz, de Leon, & Diaz, 2008; Waller & Ruddock, 1995), and six studies indicated that women with BN had greater AB to food cues compared to healthy controls (Ben-Tovim & Walker, 1991; Ben-Tovim, Walker, Fok, & Yap, 1989; Cooper & Todd, 1997; Jones-Chesters, Monsell, & Cooper, 1998; Léonard, Divac, Bichindaritz, Rouer-Saporta, & Samuel-Lajeunesse, 1997; Lokken, Marx, & Ferraro, 2006). Further, all but one of the available effect sizes across both significant and non-significant findings (Black et al, 1997) indicated greater AB to food in women with BN.…”
Section: Resultsmentioning
confidence: 99%
“…Among studies using the Stroop task with food-related cues, the majority of studies found no significant differences in AB between women with BN and healthy controls (Black, Wilson, Labouvie, & Heffernan, 1997; Davidson & Wright, 2002; Flynn & McNally, 1999; Johansson, Carlbring, Ghaderi, & Andersson, 2008; Lee, Namkoong, & Jung, 2017; Lovell, Williams, & Hill, 1997; Perpiñá, Hemsley, Treasure, & de Silva, 1993; Perpiña, Leonard, Treasure, Bond, & Banos, 1998; Ruiz, de Leon, & Diaz, 2008; Waller & Ruddock, 1995), and six studies indicated that women with BN had greater AB to food cues compared to healthy controls (Ben-Tovim & Walker, 1991; Ben-Tovim, Walker, Fok, & Yap, 1989; Cooper & Todd, 1997; Jones-Chesters, Monsell, & Cooper, 1998; Léonard, Divac, Bichindaritz, Rouer-Saporta, & Samuel-Lajeunesse, 1997; Lokken, Marx, & Ferraro, 2006). Further, all but one of the available effect sizes across both significant and non-significant findings (Black et al, 1997) indicated greater AB to food in women with BN.…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence in non‐musical domains showed that the relevance of the task for a given subject plays a role in modulating the SCR (Dindo & Fowles, 2008; Epstein & Fenz, 1962; Fenz & Epstein, 1962; Lang et al, 1998; Ohman & Soares, 1994; Perpina, Leonard, Bond, Bond, & Banos, 1998; Stormark, Laberg, Nordby, & Hugdahl, 2000). These studies, carried out with psychiatric patients and normal volunteers, revealed that higher SCRs specific to a given object were dependent on individual experience.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, phobic subjects produce larger SC‐ORs to phobia‐relevant stimuli than to control stimuli (e.g., Wilson, 1967), even with brief stimulus presentations that preclude conscious awareness (Öhman & Soares, 1994; Öhman & Wiens, 2003). Perpina, Leonard, Treasure, Bond, and Banos (1998) reported larger SCRs to words related to food and body image among female patients with an eating disorder.…”
mentioning
confidence: 88%